American militias : state-level variations in militia activities - Freilich, Joshua D. (Criminal justice (LFB Scholarly Publishing LLC), 2003)
Freilich attempts to determine why some states have higher levels of militia activity than others. Focusing on the years 1994-1995, he finds that cultural factors-not economic conditions--are related to levels of militia related activity. In particular, states with lower levels of female empowerment and higher levels of paramilitary culture were more likely to have more militia groups. Conversely, neither economic dislocation/social disorganization nor economic prosperity/social integration were related to the number of militia groups on the state level. These findings suggest that programs seeking to preempt militia formation by providing economic assistance will not be successful. Instead, such programs must confront cultural issues as well.